Batas Aurat Muslimah Limits Of Muslimah Aurat - Karunia, Khaerunnisa; Suhufi, Muh; M, Misbahuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The debate about the boundaries of women's private parts has continued from classical to modern times. This is because the problem of limiting women's private parts has implications for other problems, such as wearing the veil, women's voices and women's interactions with men. This article aims to examine in detail the limits of women's private parts and other matters related to it. The research carried out was qualitative research through literature study. The research was conducted by analyzing the concept and boundaries of women's private parts according to the opinions of 4 schools of thought, namely the Hanafi, Maliki, Syafii and Hanbali schools. Apart from that, it also examines the opinions of contemporary scholars regarding women's private parts. This article concludes that within the boundaries of women's private parts, there are things that the ulama agree on and there are also things where the ulama have different opinions on them.